2017
DOI: 10.1051/matecconf/201710601013
|View full text |Cite
|
Sign up to set email alerts
|

Kohonen cards for clustering fund of the residential real-estate

Abstract: Abstract. The algorithm of a clustering of fund of the residential realestate is based on a neural network simulation using T. Kokhonnen's maps. Self-organizing maps (SOM) divide 296 objects into 16 clusters based on 33 signs. An important result of the research is the possibility of structural analysis of housing stock which allows to form an idea of his general condition. During periodic inspection and analysis of the condition of housing stock relocation of an object in other cluster will specify the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This helps to facilitate quick decisions by investors, buyers, government and financial institutions. [95] Identification of opportunities in real estate market [96] Incorporation of energy demand in real estate valuation [97] Image classification of interior of properties [98] Image classification of both interior and exterior of buildings [99] Clustering of fund of real estate derived via valuation [100] Management of real estate information [101] Core competence estimation of real estate firms [102] Core competence estimation of real estate firms [103] Selection of tax check in real estate firms [104] Development of decision support system for evaluation [105] Auditing of real estate evaluation process [106] Real estate problem solving [107] Comparison of ANN over other methods showed that despite the predictive capability of ANN, some other models performed better than it. SVM performed better than ANN for small training data [89].…”
Section: Price Prediction and Forecasting Of Real Estatementioning
confidence: 99%
“…This helps to facilitate quick decisions by investors, buyers, government and financial institutions. [95] Identification of opportunities in real estate market [96] Incorporation of energy demand in real estate valuation [97] Image classification of interior of properties [98] Image classification of both interior and exterior of buildings [99] Clustering of fund of real estate derived via valuation [100] Management of real estate information [101] Core competence estimation of real estate firms [102] Core competence estimation of real estate firms [103] Selection of tax check in real estate firms [104] Development of decision support system for evaluation [105] Auditing of real estate evaluation process [106] Real estate problem solving [107] Comparison of ANN over other methods showed that despite the predictive capability of ANN, some other models performed better than it. SVM performed better than ANN for small training data [89].…”
Section: Price Prediction and Forecasting Of Real Estatementioning
confidence: 99%
“…The data clustering method considered in this work was applied in a number of works and used to assess the transport infrastructure of the city, housing stock, investment and social attractiveness of urban areas, and to draw up a schedule of building repairs [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%